Social and cultural relations are inherent in the life of the Semparu Community, Lombok - Nasikhatul Ulla Al Jamiliyati (Privietlab, 2025)
This study examines the social and cultural relations inherent in the lives of the Semparu community in Central Lombok. The Semparu community is known for its strong kinship ties, traditions of mutual cooperation, and cultural practices that form the basis of social cohesion. This study aims to understand how local values function in maintaining solidarity, collective identity, and cultural sustainability amidst the currents of modernization. The method used is a qualitative approach with ethnographic types through participant observation, in-depth interviews, and documentation. Data analysis was conducted using the interactive model of Miles and Huberman, and its validity was tested through triangulation of sources and methods. The research findings show that social relations within the Semparu community are built on trust, reciprocity, and solidarity, manifested in collective practices such as gawe (celebrations), community service, and mutual assistance among the community members. This inherent culture is evident in the traditional rituals and life cycle traditions maintained by traditional leaders, religious figures, and village elders as agents of value transmission. However, modernization and globalization present challenges, including shifts in cultural meaning, ambivalence among the younger generation, and the risk of weakening traditional regeneration. Nevertheless, the Semparu community demonstrates cultural resilience by adapting without losing its essence. This research concludes that the inherent social and cultural relations in Semparu are still maintained as social capital and collective identity, despite facing the pressures of modernization. Its sustainability depends on community-based preservation strategies involving community leaders, the younger generation, and cultural education.